Designating Spatial Priorities for Marine Biodiversity Conservation in the Coral Triangle - Asaad, Irawan; Lundquist, Carolyn J.; Erdmann, Mark V.; Van Hooidonk, Ruben; Costello, Mark J. (Frontiers in Marine Science, 2018)
To date, most Marine Protected Areas (MPA) have been designated on an ad hoc basis. However, a comprehensive regional and global network should be designed to be representative of all aspects of biodiversity, including populations, species, and biogenic habitats. A good exemplar would be the Coral Triangle (CT) because it is the most species rich area in the ocean but only 2% of its area is in any kind of MPA. Our analysis consisted of five different groups of layers of biodiversity features: biogenic habitat, species richness, species of special conservation concern, restricted range species, and areas of importance for sea turtles. We utilized the systematic conservation planning software Zonation as a decision-support tool to ensure representation of biodiversity features while balancing selection of protected areas based on the likelihood of threats. Our results indicated that the average representation of biodiversity features within the existing MPA system is currently about 5%. By systematically increasing MPA coverage to 10% of the total area of the CT, the average representation of biodiversity features within the MPA system would increase to over 37%. Marine areas in the Halmahera Sea, the outer island arc of the Banda Sea, the Sulu Archipelago, the Bismarck Archipelago, and the Malaita Islands were identified as priority areas for the designation of new MPAs. Moreover, we recommended that several existing MPAs be expanded to cover additional biodiversity features within their adjacent areas, including MPAs in Indonesia (e.g., in the Birds Head of Papua), the Philippines (e.g., in the northwestern part of the Sibuyan Sea), Malaysia (e.g., in the northern part of Sabah), Papua New Guinea (e.g., in the Milne Bay Province), and the Solomon Islands (e.g., around Santa Isabel Island). An MPA system that covered 30% of the CT would include 65% of the biodiversity features. That just two-thirds of biodiversity was represented by one-third of the study area supports calls for at least 30% of the ocean to be in no-fishing MPA. This assessment provides a blueprint for efficient gains in marine conservation through the extension of the current MPA system in the Coral Triangle region.